Performance evaluation of a paddy drum seeder in a farmer's field in Chamravattom of Malappuram district - BINOY K.M JAYASANKAR S. KAIMAL; Dr. Jayan P.R (Guide) (Tavanur 2006 Kelappaji College of Agricultural Engineering and Technology)
Performance evaluation of a paddy drum seeder in a farmer's field in Chamravattom of Malappuram district
Performance evaluation of a paddy drum seeder in a farmer's field in Chamravattom of Malappuram district